TRPA1 channels mediate acute neurogenic inflammation and pain produced by bacterial endotoxins - Meseguer, Victor; Alpizar, Yeranddy A.; Luis, Enoch; Tajada, Sendoa; Denlinger, Bristol; Fajardo, Otto; Manenschijn, Jan-Albert; Fernandez-Pena, Carlos; Talavera, Arturo; Kichko, Tetyana; Navia, Belen; Sanchez, Alicia; et al. (Nature Communications, 2014)
Gram-negative bacterial infections are accompanied by inflammation and somatic or visceral pain. These symptoms are generally attributed to sensitization of nociceptors by inflammatory mediators released by immune cells. Nociceptor sensitization during inflammation occurs through activation of the Toll-like receptor 4 (TLR4) signalling pathway by lipopolysaccharide (LPS), a toxic by-product of bacterial lysis. Here we show that LPS exerts fast, membrane delimited, excitatory actions via TRPA1, a transient receptor potential cation channel that is critical for transducing environmental irritant stimuli into nociceptor activity. Moreover, we find that pain and acute vascular reactions, including neurogenic inflammation (CGRP release) caused by LPS are primarily dependent on TRPA1 channel activation in nociceptive sensory neurons, and develop independently of TLR4 activation. The identification of TRPA1 as a molecular determinant of direct LPS effects on nociceptors offers new insights into the pathogenesis of pain and neurovascular responses during bacterial infections and opens novel avenues for their treatment.
EVALuna2:2452